Qualitative and quantitative analysis of self-care regarding sensory issues among people with neurodevelopmental disorders - Wada, Makoto; Hayashi, Katsuya; Seino, Kai; Ishii, Naomi; Nawa, Taemi; Nishimaki, Kengo (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction Issues in sensory processing (hereafter, sensory issues) associated with neurodevelopmental disorders are known to be particularly prominent from 6 to 9 years of age and are a critical issue in school life. These issues affect each individual's quality of life. Some of the issues are known to be relieved by self-care while some are not. Methods To clarify the sensory issues that cannot be managed by self-care, this study examined self-care for sensory issues among people with neurodevelopmental disorders using a web survey. The survey encompassed questions about neurodevelopmental disorders, the sensory issues individuals experience, and the kind of self-care they perform. In the qualitative analysis, each was categorized by the type of sensory modality; we further scrutinized the descriptions of self-care, which were collected simultaneously, and examined how each problem was addressed. Results Self-care was categorized as “physically blocking,” “leaving from,” “relaxing,” “devising,” “help from others,” “taking medication,” “coping with body,” “others,” or “could not cope.” Based on these findings, we quantitatively compared the frequency of sensory issues that could and could not be managed by self-care. Consequently, significantly higher percentages of the participants stated that they experienced difficulties in managing problems about “body representations,” “contact with humans,” “selective listening,” and “force control.” In contrast, significantly more participants stated that they could manage problems related to “loud sound” and “dazzling”. Conclusion In this study, qualitative analysis allowed us to categorize methods of self-care for sensory issues, and quantitative research allowed us to identify issues that were difficult to manage. While it was possible to manage strong light and sound using sunglasses, earplugs, and so on, problems related to the senses of proprioception, selective attention, and so on were clearly difficult to manage.